Intercellular nanotube-mediated mitochondrial transfer enhances T cell metabolic fitness and antitumor efficacy - Baldwin, Jeremy G.; Heuser-Loy, Christoph; Saha, Tanmoy; Schelker, Roland; Slavkovic-Lukic, Dragana; Strieder, Nicholas; Hernandez-Lopez, Inmaculada; Rana, Nisha; Barden, Markus; Mastrogiovanni, Fabio; Martín-Santos, Azucena; Raimondi, Andrea; et al. (Cell, 2024)
Mitochondrial loss and dysfunction drive T cell exhaustion, representing major barriers to successful T cell-based immunotherapies. Here, we describe an innovative platform to supply exogenous mitochondria to T cells, overcoming these limitations. We found that bone marrow stromal cells establish nanotubular connections with T cells and leverage these intercellular highways to transplant stromal cell mitochondria into CD8+ T cells. Optimal mitochondrial transfer required Talin 2 on both donor and recipient cells. CD8+ T cells with donated mitochondria displayed enhanced mitochondrial respiration and spare respiratory capacity. When transferred into tumor-bearing hosts, these supercharged T cells expanded more robustly, infiltrated the tumor more efficiently, and exhibited fewer signs of exhaustion compared with T cells that did not take up mitochondria. As a result, mitochondria-boosted CD8+ T cells mediated superior antitumor responses, prolonging animal survival. These findings establish intercellular mitochondrial transfer as a prototype of organelle medicine, opening avenues to next-generation cell therapies.
CRIS-Team Scopus Importer:2024-11-08
Keywords: bone marrow stromal cells; cancer immunotherapy; CAR T therapy; CD8; immune metabolism; mitochondrial transfer; nanotubes; Talin 2; TCR-T therapy; TIL therapy